Model for Empowering Traditional Leaders in Resolving Customary Conflicts Based on Local Wisdom in Indonesia - Setiawati Setiawati (Jurnal Pemberdayaan Masyarakat, 2025)
Customary conflicts in Indonesia continue to escalate as the strategic value of land and natural resources in customary areas increases. The existence of customary institutions and customary leaders as conflict resolution actors is often marginalized by the dominance of state law, which is not always compatible with local value systems. This study aims to develop a conceptual model for empowering traditional leaders in resolving customary conflicts, grounded in the principles of legal pluralism, restorative justice, and community empowerment. The research employs a normative-empirical legal method with a descriptive qualitative approach, grounded in a comprehensive literature review of national and international sources. The study's results indicate that the social legitimacy of indigenous leaders, regional regulatory support, and the synergy between indigenous institutions and village governments have a significant influence on the effectiveness of indigenous conflict resolution. The proposed empowerment model encompasses strengthening the legal basis of traditional deliberations, enhancing the mediation capacity of traditional leaders, mapping traditional territories, and promoting active participation in investment decision-making. These findings are expected to contribute academically and practically to strengthening traditional institutions in the governance of agrarian conflict resolution in Indonesia.